Demonstrating the BlackBerry as a Clinical Communication Tool: A Pilot Study Conducted through the Centre for Innovation in Complex Care - Sherman Quan, Robert Wu, Dante Morra, Brian M. Wong, Richard Mraz, Melinda Hamill, Howard Abrams and Peter G. Rossos (ElectronicHealthcare, 2008)
Canadians are living longer with chronic medical conditions, which have led to an increasing complexity and volume of care for hospitalized patients. Effective in-patient care depends on the effective coordination of care through rapid and efficient communication between various care providers. A delay in coordinating this care has downstream effects on other parts of the system, ultimately contributing to increased emergency department wait times. To address this system-wide issue, the Centre for Innovation in Complex Care at the University Health Network collaborated with Sunnybrook Health Sciences Centre to pilot the use of BlackBerry devices on the general internal medicine wards to improve clinical communication. We describe the implementation process, impact on clinical care and lessons learned from this experience. We observed that residents quickly adopted this new technology and felt that it improved their workflow efficiency and productivity.
Keywords: BlackBerry, complex care, innovation, device, healthcare information technology